2000
DOI: 10.1046/j.1460-9568.2000.00152.x
|View full text |Cite
|
Sign up to set email alerts
|

Early postnatal maturation of GABAA‐mediated inhibition in the brainstem respiratory rhythm‐generating network of the mouse

Abstract: It is well established that GABAA-mediated postsynaptic potentials are excitatory in many brain regions during embryonic and early postnatal life. The pre-Bötzinger complex (PBC) in the brainstem is an essential component of the respiratory rhythm-generating network, where GABAA-mediated inhibition plays a critical role in generating a stable respiratory rhythm in adult animals. In the present study, using the perforated patch technique, we investigated the maturation of GABAA receptor-mediated effects on rhyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
102
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(107 citation statements)
references
References 37 publications
3
102
2
Order By: Relevance
“…Rather, it has been reported that the GABA A -mediated response switches from depolarization to hyperpolarization during the first postnatal week (Ritter and Zhang, 2000). However, the present results demonstrated the existence of inhibitory neural activity in the facial nucleus bilaterally in the wild-type E18.5 fetus under adrenaline-stimulated condition (Fig.…”
contrasting
confidence: 72%
“…Rather, it has been reported that the GABA A -mediated response switches from depolarization to hyperpolarization during the first postnatal week (Ritter and Zhang, 2000). However, the present results demonstrated the existence of inhibitory neural activity in the facial nucleus bilaterally in the wild-type E18.5 fetus under adrenaline-stimulated condition (Fig.…”
contrasting
confidence: 72%
“…Glutamatergic transmission is obligatory for rhythmogenesis in vitro (26,27), whereas inhibitory transmission is not (28,29). Synaptic inhibition nonetheless regulates the amplitude of XII motor output (10,11). To focus on the role of glutamatergic neurons, we performed these experiments in the presence of picrotoxin and strychnine.…”
Section: Discussionmentioning
confidence: 99%
“…We were able to image to a depth of 80 μm by using Ti:sapphire laser pulses in both slice types. Synaptic inhibition is not essential for rhythmogenesis in vitro, but it influences the amplitude of XII output (10,11). Therefore, we added 5 μM strychnine and picrotoxin to the artificial cerebrospinal fluid (ACSF) before the detection phase so that XII output would be insensitive to the effects of laser-ablating inhibitory neurons (12,13) during the ablation phase.…”
Section: Detecting Inspiratory Neurons In the Prebötc And Ventral Resmentioning
confidence: 99%
“…natal maturation of GABAergic inhibitory transmission (Ritter and Zhang, 2000). First, we have identified a bilateral rhythm generation site spatially restricted in a region ventral to the nucleus ambiguus, the activity of which is preserved in a transverse slice (Smith et al, 1991).…”
Section: The Hf Generator Is the Respiratory Generatormentioning
confidence: 99%